Contribution of Stock Market Development on Economic Growth of Nepal (Economic Journal of Nepal, 2021)
The paper is to analyze the contribution of stock market development on economic growth of Nepal. A well-developed stock market could promote the volume of domestic savings, saving mobilization, capital formation, and efficient allocation of capital in productive sectors of the economy that ultimately helps for increasing income, output, and employment and thereby enhance the economic growth of the nation. The study followed quantitative analysis and deductive method by using secondary data of 27 years from 1994 to 2021. It used ARDL model, co-integration test, bound test, CUSUM, and CUSUMQ test for data analysis. It employs the real gross domestic product as a proxy variable for economic growth while broad money supply, market capitalization, stock market turnover, NEPSE index, and listed companies are taken as the indicator of stock market development. The study found that there is a significant contribution of broad money supply, market capitalization and NEPSE index to real GDP. But, there is a weak contribution of stock market turnover to real GDP that indicates a liquidity problem in Nepalese stock market. It concludes that stock market development has a significant contribution for economic growth in Nepal. Hence, it is suggested that policymakers should think about the stock market development for the economic growth of Nepal.